Non-thermal atmospheric dielectric barrier discharge plasma, medical application studies in Thailand - Chanchai Chutsirimongkol (2018)
© 2016 by Begell House, Inc. Atmospheric Dielectric Barrier Discharge (DBD) plasma development is one of the most interesting subjects to our group. Fridman et al.* has concluded that Floating DBD Direct Plasma are more effective in bactericidal property, it contains higher free charged particles than indirect type. DBD plasma sources can provide low temperature or non-thermal (cold) plasmas, and these plasmas can be created with ambient air or with a noble gas, such as helium or argon, as the carrier medium. It can be used with an electrode as a contact or noncontact method to target a tissue. However, the drawback of direct DBD plasma is that it will work only in short gap distances, on the order of a few millimeters. Our group has investigated the clinical safety and efficacy of a novel DBD non-thermal atmospheric plasma source (BIOPLASMA Cell Modulation: PhotoBioCare, Thailand). The major area has been focused on its bactericidal disinfection property, application in common dermatologic problems, in skin aesthetic facial rejuvenation and chronic wound management, from 2012 to 2016.